Adipose-derived human mesenchymal stem cells induce long-term neurogenic and anti-inflammatory effects and improve cognitive but not motor performance in a rat model of Parkinson's disease. (May 2015) - Schwerk, Anne; Altschüler, Jennifer; Roch, Manfred; Gossen, Manfred; Winter, Christine; Berg, Jürgen; Kurtz, Andreas; Akyüz, Levent; Steiner, Barbara
Background: Mesenchymal stem cells (MSC) are easily harvested, and possess anti-inflammatory and trophic properties. Furthermore, MSC promote neuroprotection and neurogenesis, which could greatly benefit neurodegenerative disorders, such as Parkinson's disease.Methods: MSC were transplanted one week after 6-hydroxydopamine lesioning and effects were evaluated after 6 months.Results: MSC localized around the substantia nigra and the arachnoid mater, expressing pericyte and endothelial markers. MSC protected dopamine levels and upregulated peripheral anti-inflammatory cytokines. Furthermore, adipose-derived MSC increased neurogenesis in hippocampal and subventricular regions, and boosted memory functioning.Conclusion: Considering that hyposmia and loss of memory function are two major nonmotor symptoms in Parkinson's disease, transplants with modulatory effects on the hippocampus and subventricular zone could provide a disease-modifying therapy.